Abundant presolar silicates of the CM chondrite Asuka 12169: Implications for the thermal and aqueous alteration of the CM parent body. (1st October 2022) - Xu, Yuchen; Lin, Yangting; Hao, Jialong; Kimura, Makoto; Hu, Sen; Yang, Wei; Liu, Yang; Zou, Yongliao
Abstract: The solar system could be separated into two zones based on the isotopic dichotomy between non-carbonaceous and carbonaceous groups, with the latter likely accreted in the outer solar system. Among carbonaceous groups, the CM chondrite contains high abundances of organic carbon and water. They have undergone aqueous alteration, thermal metamorphism and brecciation to different degrees (e.g., Rubin et al., 2007; Tonui et al., 2014; Zolensky et al., 1997), which contributed to erasing most of the solar nebular records. Asuka 12169 was reported as the most primitive CM chondrite based on petrological and geochemical results, with little aqueous alteration (Kimura et al., 2020). In this paper, we report a survey of presolar grains in the fine-grained matrix and the accretionary rims of chondrules and CAIs in this meteorite, based on NanoSIMS mapping of C-, O-, and Si-isotopes. A total of 158 presolar grains were identified, including 119 silicates/oxides (208 ± 20 ppm), 38 SiC (73 ± 12 ppm) and 1 carbonaceous grain ( 2 - 2 + 5 ppm). These abundances are within the maximum abundance ranges of primitive chondrites (80–280 ppm for O-rich grains and 10–180 ppm for C-rich grains). In comparison with most CM chondrites (<40 ppm), Asuka 12169 is uniquely rich in presolar silicates (185 ± 18 ppm), with a high presolar silicate/oxide ratio of ∼8, therefore providing robust evidence for little aqueous alteration. The high abundances of presolar SiC and silicates in Asuka 12169 clearly show its pristine properties regarding both thermal and aqueous alteration. Group 1, 2, 3 and 4 subtypes of presolar O-rich grains account for 84%, 2.5%, 0.8% and 12.6%, respectively. One O-rich grain shows a high enhancement in 17 O/ 16 O and a subsolar 18 O/ 16 O ratio ( 17 O/ 16 O = 6.45 ± 0.09 × 10 −3 and 18 O/ 16 O = 1.90 ± 0.02 × 10 −3 ), indicating a stellar origin in binary star systems or novae. Most identified presolar SiC are mainstream grains of AGB origins. One with 28 Si-excess is classified as an X grain, suggesting a supernova origin. There are two SiC grains that have 12 C/ 13 C < 10 but close-to-solar Si isotopic ratios, and are therefore classified as AB type. The pristine features of Asuka 12169 suggest that it was probably located in the outermost few kilometers of the CM asteroid, where temperature was high enough for sublimation of water ice under vacuum, but where no aqueous alteration occurred, and where the depth was enough for lithification. The high abundances of various types of presolar grains, together with the petrographic information of Asuka 12169, provide crucial constrains on the original properties and subsequent evolution of the CM asteroids.